Comparative characteristic of Bi- and La- doped (Ca/Sr)MoO4 -based materials with a defect scheelite-type structure - Zoya A. Mikhaylovskaya; Alexandra V. Klimova; Sofia A. Petrova; Elizaveta A. Pankrushina; Elena S. Buyanova (Chimica Techno Acta)
CaMoO4- and SrMoO4-based scheelite-type phases are noteworthy functional materials, whose properties strongly correlate with their structure. This work is devoted to La- or Bi-doped scheelite-type molybdates. The purpose of the present study is to quantify the effect of isolated electron pairs of bismuth on the distortion of the structure and related properties. Conventional solid-state technology was used for the synthesis of (Ca/Sr)1–3xLa2xФxMoO4 and Sr1–3xBi2xФxMoO4, (0.025≤ x ≤ 0.275). The structure was investigated by X-ray powder diffraction and Raman spectroscopy. Rates of structure distortion were characterised by the analysis of the autocorrelation function (AAF) of Raman spectra. Energy gaps were calculated by the Kubelka-Munk method. The conductivity was studied with a.c. impedance spectroscopy. For (Ca/Sr)1−3x(Bi/La)2xФxMoO4 series 0.025 ≤ x ≤ 0.15 compositions show a basic defect scheelite structure, while 0.15 x ≤ 0.225 compositions of Bi-doped samples exhibit tetragonal supercells. The chemical compression of unit cell is more evident in the case of Bi-doping, indicating the preferred orientation of the isolated electron pairs. The distortion of MoO4 polyhedra showed by AAF was more significant for Sr1−3xBi2xФxMoO4 than for Sr1−3xLa2xФxMoO4, the Δcorr parameters for Bi-doped compositions were almost double in comparison with La-doped one in the range of 50–600 cm–1 of the Raman shift. The «critical» x = 0.15 point was also clearly indicated by Δcorr parameter. The AAF of the Raman spectra of solid oxides was shown to be a good tool for prediction of properties and points of phase transitions in solid oxides.